PENCEGAHAN TINDAK PIDANA KORUPSI PADA BIRO SARANA PRASARANA KEPOLISIAN DAERAH SUMATERA BARAT MELALUI PENERAPAN SISTEM ELEKTRONIK PENGADAAN BARANG/JASA - Mairust, Supriadi (LPPM Universitas Ekasakti Padang, 2019)
The West Sumatra Regional Police has implemented the procurement of auctions electronically through the West Sumatra Regional Police Infrastructure Bureau. Deviations in the process of procuring goods and services that are detrimental to state finances are a form of corruption. Efficient and effective procurement of government goods / services is an important part of improving state financial management. One of the manifestations is by implementing the process of procurement of government goods / services electronically. This research is a descriptive analytical study. The implementation of the electronic system for the procurement of goods / services auction at the West Sumatra Regional Police Infrastructure Bureau has provided all data and information stored by the LPSE Polri or LPSE Polda to be connected to the national goods / services procurement information center at LKPP as the national procurement portal manager. LKPP, as the manager of the national procurement portal, has the authority to provide guidance and supervision over the implementation of procurement of goods / services electronically within the Indonesian National Police. All costs incurred in managing LPSE are borne by the National Police DIPA. Constraints encountered in the application of electronic systems for the procurement of goods / services at the West Sumatra Regional Police Infrastructure Bureau were due to factors such as: Internal Constraints and External Constraints